Modelagem dinâmica e controle de aeronaves multirrotoras com configuração Tilt Rotor para transporte de líquidos - Tarifa, Ivan Oliveira (2022)
The use of aircraft for pesticide application is becoming increasingly common nowadays, especi- ally with multirotors, due to their precision and versatility. The application of defensibles can be represented by a liquid mass that makes up a large part of the aircraft weight, making the center of mass change during flight, as well as creating the sloshing effect. Structures can be inserted into the container to mitigate these effects. However, robust controls can save space and money. Thus, one of the objectives of this work was the development of a unified model of simulation of liquid transport together with the dynamics of a multirotor aircraft through easy-to-use open codes, to enable the development and testing of different control laws. In addition, tilts were used in the multirotor aircraft to investigate their effect on liquid cargo transport, along with the influence of sloshing on the aircraft’s flight dynamics by fluid-structure interaction. This work has two simulation experiments: one being a comparison with experimental results for a box with fluid subjected to external accelerations and the other a comparison of aircraft control with and without the fluid box. In the first one, it was observed that despite some simplifications made in the model, the pressure values on the wall had similar behaviour to the existing experimental ones. For the second, an experiment with step input was carried out, and it was possible to observe the influence of sloshing on the aircraft’s flight dynamics as well as the tilts.